Whole transcriptome sequencing reveals a TCF4-ZNF384 fusion in acute lymphoblastic leukemia - Wu, Zhengyu; Zhang, Fang; Liu, Chengzhu; Shen, Shuhong; Chu, Jinhua; Yang, Linhai; Xie, Zhiwei; Liu, Yu; Liu, Kangkang; Wang, Ningling (Frontiers in Oncology, 2022)
Previous studies have shown that ,the clinical features and prognosis of ZNF384-rearranged pediatric acute lymphoblastic leukemia (ALL) depend on its translocation partners. We report two cases of TCF4-ZNF384 fusion, one 6-year-old girl and one 10-year-old boy, both diagnosed by whole-transcriptome sequencing, and TCF4 is the newest fusion partner of ZNF384. As illustrated in this first report of TCF4-ZNF384 fusion in ALL patients, the identification of patients with ZNF384 rearrangement in ALL patients is critical to elucidate outcomes associated with a specific rearrangement and to develop appropriate treatment strategies. In addition, the development of other methods to detect ZNF384 specific translocation partners and leukemia specific targeting agents is of great significance to further improve the prognosis of ALL with ZNF384-rearrangement.